EKSTRAKSI MINYAK NILAM (Pogostemon Cablin BENTH) DENGAN TEKNIK HIDRODIFUSI PADA TEKANAN 1 – 3 BAR - Niken Harimurti; Tatang H Soerawidjaja; Djajeng Sumangat; nFN Risfaheri (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2012)
ABSTRACT. Niken Harimurti, Tatang H Soerawidjaja, Djajeng Sumangat and Risfaheri. 2012. Patchouly oil extraction with hydrodiffusiontechnique at 1 – 3 bar pressure. Patchouli oil is a type of essential oil which was obtained by pressured steam or water distillation of Pogostemoncablin Benth dried leaves. Key components of patchouli oil are patchouli alcohol and norpatchoulenol which become indicators in determiningpatchouli oil quality. This research was objected to evaluate patchouli oil extraction with hydrodiffusion technique at 1-3 bar pressure. This experimentwas designed with response surface method, with pressure (Low level 1 bar, high level 3 bars) and time (low level 3 hours, high level 12 hours) asvariables. Yield, density, refractive index, optical polarization, solubility in ethanol 90%, acid number and ester number were evaluated as the responsof the two variables. Analysis of respons surface method showed that increasing extraction pressure significantly influence in acid number while theyield of patchouli oil was influenced by pressure, time and interaction of both. Results of qualitative analysis by GC / MS showed that oil samples atno 11 (pressure 3 bar for 3 hours) contained patchouli alcohol 29.66% and norpatchoulenol 0.68%. Microhistology identification of patchouli leavesbefore and after extraction showed reduction of glandular trichomas diameter about 61.2%. Based on quality parameters values, statistical and GC /MS analysis results, the best condition for hydrodiffusion process was at 3 bar pressure for 3 hours.Keywords: patchouli oil, hydrodiffusion, patchouli alcohol, norpatchoulenol